Cover with caution: Management of the Left Subclavian Artery in TEVAR for trauma. Issue 3 (29th March 2023) - Romagnoli, Anna Noel; Paterson, Jeanette; Dua, Anahita; Kauvar, David; Saqib, Naveed; Miller, Charles; Starnes, Benjamin; Azizzadeh, Ali; DuBose, Joseph
Abstract : Higher rate of ischemic neurologic events in left subclavian artery coverage in TEVAR for BTAI than previously observed in trauma literature. #BTAI, #TEVARfortrauma, #aortictraumafoundation Abstract : BACKGROUND: Elective Thoracic Endovascular Aortic Repair (TEVAR) with left subclavian artery coverage (LSA-C) without revascularization is associated with increased rates of ischemic stroke. In patients with blunt thoracic aortic injury (BTAI) requiring TEVAR, LSA-C is frequently required in over one-third of patients. This study aimed to evaluate outcomes of TEVAR in BTAI patients with and without LSA-C. METHODS: The largest existing international multicenter prospective registry of BTAI, developed and implemented by the Aortic Trauma Foundation, was utilized to evaluate all BTAI patients undergoing TEVAR from March 2016 to January 2021. Patients with uncovered left subclavian artery (LSA-U) were compared with patients who had left subclavian artery coverage with (LSA-R) and without (LSA-NR) revascularization. RESULTS: Of the 364 patients with BTAI who underwent TEVAR, 97 (26.6%) underwent LSA-C without revascularization, 10 (2.7%) underwent LSA-C with revascularization (LSA-R). Late and all ischemic strokes were more common in LSA-NR patients than LSA-U patients ( p = 0.006, p = 0.0007). There was no difference in rate of early, late, or overall incidence of paralysis/paraplegia between LSA-NR and LSA-U. When compiled as composite central nervous system ischemic sequelae, there was an increased rate in early, late, and overall events in LSA-NR compared with LSA-U ( p = 0.04, p = 0.01, p = 0.001). CONCLUSION: While prior studies have suggested the relative safety of LSA-C in BTAI, preliminary multicenter prospective data suggests there is a significant increase in ischemic events when the left subclavian artery is covered and not revascularized. Additional prospective study and more highly powered analysis is necessary. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :